1982
DOI: 10.1111/1523-1747.ep12497854
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Tissue Plasminogen Activator from Skin Lesions with Allergic Vasculitis

Abstract: A tissue plasminogen activator was extracted from skin lesions with allergic vasculitis and purified by successive column chromatography on Sephadex G-200, DEAE-cellulose, Hydroxyaptite-cellulose and polyacrylamide gel electrophoresis. By these procedures, 160 micrograms of enzyme with a specific activity of 843.8 international units/mg protein was obtained from 5 g of original skin. The purified material was homogeneous as ascertained by sodium dodecyl sulfate polyacrylamide gel electrophoresis and had an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Miskin and Ben-Ishai (1981) found that UV light induced u-PA in fibroblasts from patients with xeroderma pigmentosum, Toki et al (1982) purified u-PA from skin lesions with allergic vasculitis, and Hashimoto et al (1983) found that binding of pemphigus auto-antibodies to human epidermal cells resulted in elevated levels of u-PA. Furthermore, the type of plasminogen activator reported to be associated with inflammatory diseases has been u-PA (Unkeless et al, 1974a;Dane et al, 1985). Therefore, the present finding of t-PA as the only detectable plasminogen activator in psoriatic scales is remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…Miskin and Ben-Ishai (1981) found that UV light induced u-PA in fibroblasts from patients with xeroderma pigmentosum, Toki et al (1982) purified u-PA from skin lesions with allergic vasculitis, and Hashimoto et al (1983) found that binding of pemphigus auto-antibodies to human epidermal cells resulted in elevated levels of u-PA. Furthermore, the type of plasminogen activator reported to be associated with inflammatory diseases has been u-PA (Unkeless et al, 1974a;Dane et al, 1985). Therefore, the present finding of t-PA as the only detectable plasminogen activator in psoriatic scales is remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmin generated by uPA participates in the turnover of extracellular matrix proteins in physiological and pathophysiological tissue remodeling 1, 2 . Abnormal expression of uPA is responsible for tissue damage in several pathological conditions, including rheumatoid arthritis 3 , allergic vasculitis 4 , xeroderma pigmentosum 5 , atherosclerosis 6 , and in particular, is a key factor for the invasive capacity of malignant tumours 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Disturbance of the eqUilibrium between fibrin deposition and its removal by the fibrinolytic system, for example because of an increase in inhibitors and/or activator deficit, can result in accumulation of fibrin in the derma, as seen in numerous dermatologic affections: bullous dermatoses of the pemphigoid group (RYAN 1976;PANCONESI et al 1982), lichen planus (CRAWFORD and OGSTON 1975;LOTTI and FABBRI 1984), Schamberg's purpura (LoTTI et al 1985 b), and cutaneous vasculitis (CUNLIFFE 1968;TOKI et al 1982;LOTTI et al 1985c). There is instead an increase in fibrinolytic activity with excessive removal of fibrin from the microvessels which causes increased permeability of the dermal vessels in other diseases, such as urticaria (RYAN 1976;LOTTI et al 1985c), Majocchi's purpura (LOTTI et al 1985b), porphyria cutanea tarda (CHIMENTI et al 1981), psoriasis (RYAN 1973(RYAN , 1980BRUNETTI and LOTTI 1983), pemphigus vulgaris (PANCONESI et al 1982;HASHIMOTO et al 1982HASHIMOTO et al , 1984, primary irritant dermatitis , and pruritus aquagenicus (LOTTI et al 1984a(LOTTI et al , 1986b.…”
Section: Physiopathology Of the Cutaneous Fibrinolytic Systemmentioning
confidence: 99%